A concept for actuating and controlling a leg of a novel walking parallel kinematic machine tool - Rushworth, Adam; Axinte, Dragos; Raffles, Mark; Cobos-Guzman, Salvador (Elsevier, 2016)
The scope of this paper is to present a novel method of actuating the legs of a walking parallel kinematic machine tool (WalkingHex) such that the upper spherical joint can be actively driven while walking and remain a free, passive joint while performing machining operations. Different concepts for the number of Degrees of Freedom (DoF) and methods for actuating the chosen concept are presented, leading to a description of a three-wire actuated spherical joint arrangement. The inverse kinematics for the actuation mechanism is defined and a control methodology that accounts for the redundantly actuated nature of the mechanism is explored. It is demonstrated that a prototype of the system is capable of achieving a motion position accuracy within 5.64% RMS. Utilising the concept presented in this paper, it is possible to develop a walking robot that is capable of manoeuvring into location and performing precision machining or inspection operations.